Proceedings of the Ninth ACM International Conference on Web Search and Data Mining 2016
DOI: 10.1145/2835776.2835832
|View full text |Cite
|
Sign up to set email alerts
|

Improving Website Hyperlink Structure Using Server Logs

Abstract: Good websites should be easy to navigate via hyperlinks, yet maintaining a high-quality link structure is difficult. Identifying pairs of pages that should be linked may be hard for human editors, especially if the site is large and changes frequently. Further, given a set of useful link candidates, the task of incorporating them into the site can be expensive, since it typically involves humans editing pages. In the light of these challenges, it is desirable to develop data-driven methods for automating the l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 34 publications
(35 reference statements)
2
42
0
Order By: Relevance
“…The aforementioned studies assume that the manual quality assessment of Wikipedia articles and the associated reviewing processes lead to reliable ground truth about content quality. This idea has been challenged because missing links can exist for a long time (Sunercan & Birturk, 2010), links can be biased towards popularity and importance (Hanada, Cristo, & Pimentel, 2013), and links are rarely clicked (Paranjape, West, Zia, & Leskovec, 2016). This last issue is remarkable as it would be expected that appropriate links should be followed once they are created.…”
Section: Quality Of Interconnected Contentmentioning
confidence: 99%
See 4 more Smart Citations
“…The aforementioned studies assume that the manual quality assessment of Wikipedia articles and the associated reviewing processes lead to reliable ground truth about content quality. This idea has been challenged because missing links can exist for a long time (Sunercan & Birturk, 2010), links can be biased towards popularity and importance (Hanada, Cristo, & Pimentel, 2013), and links are rarely clicked (Paranjape, West, Zia, & Leskovec, 2016). This last issue is remarkable as it would be expected that appropriate links should be followed once they are created.…”
Section: Quality Of Interconnected Contentmentioning
confidence: 99%
“…This last issue is remarkable as it would be expected that appropriate links should be followed once they are created. However, Paranjape et al (2016) showed that 66% of the links are never clicked and that approximately 1% reach around 100 clicks. This may indicate flaws in the reviewing processes.…”
Section: Quality Of Interconnected Contentmentioning
confidence: 99%
See 3 more Smart Citations